Contribution of Abu Yusuf's Thoughts to Economics - Riyani Fitri Lubis (Budgeting: Jurnal Akuntansi Syariah, 2023)
Activities related to economics, especially Islamic economics, have existed since the Prophet era. The rapid and advanced development of technology supports broader economic development. Besides, it encourages Islamic thinkers to contribute their thoughts related to economics, including Abu Yusuf. Indeed, the implementation of their thoughts needs to be restudied. This article aims to review the contribution of Abu Yusuf's thoughts to economics. This library research used descriptive qualitative methods by reviewing the results of Abu Yusuf's study on economics. The results of the review showed that first, the contribution of Abu Yusuf's thoughts to economics can be found in the Book of al-Kharaj which discusses taxation and state income for example, from ghanimah, fai, kharaj, ushr, jizyah, and charity. The book also discusses the utilization of state income based on Islamic principles. Besides, it also focuses on the activities of a country including economic activities such as fiscal policy, kharaj, public finances, and price mechanisms. Second, Abu Yusuf's thoughts influence economic activities and the book of al-Kharaj is used as a reference for contemporary economic studies so far.